THE INFLUENCE OF CULTURAL CONTEXT ON LUXURY VALUE PERCEPTION AND PURCHASE INTENTION: A COMPARATIVE STUDY BETWEEN INDONESIA AND AUSTRALIA IN THE AFFORDABLE LUXURY FASHION SEGMENT - Lucky Roy Saputra; Putu Nina Madiawati; Mahir Pradana (PT. Jurnal Center Indonesia Publisher, 2026)
The rapid growth of the global affordable luxury fashion segment presents a critical paradox, as luxury brands increasingly target culturally diverse consumers who interpret the meaning of luxury in fundamentally different ways. This phenomenon becomes particularly evident when comparing collectivist markets such as Indonesia with individualistic markets such as Australia, where uniform value propositions often fail to resonate equally. This study aims to examine the influence of cultural context on Luxury Value Perception (LVP) and Purchase Intention, as well as the moderating role of Individualism–Collectivism orientation among affordable luxury fashion consumers in Indonesia and Australia. A quantitative survey-based approach was employed and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), complemented by Measurement Invariance of Composite Models (MICOM) and Multi-Group Analysis (MGA). The findings are expected to provide empirical insights into how cultural differences shape luxury value perceptions and purchase intentions, offering strategic implications for affordable luxury fashion brands in developing culturally adaptive value propositions.